Farmers’ Perception Towards Pigeon Pea Cultivation as an Alternate To Bt-Cotton In South-western Punjab - Gurdeep Singh, Pritpal Singh and Gurjinder Pal Singh Sodhi, (Indian Journal of Extension Education, 2023)
Farmers’ perception towards pigeon pea (Cajanus cajan L.) introduced in the area as an alternate for Btcottonwas assessed through yield gap and economic analysis. The magnitude of yield gap and relatedcauses for pigeon pea vary substantially, that depends upon perception of farmers towards the technologydemonstrated. Yield gap analysis for pigeon pea and Bt-Cotton was performed against crop genetic potentialand average yield at district, state and national level. Grain yield of pigeon pea (variety AL-201) variedbetween 5.8 and 8.8 q ha-1 (mean=7.5 q ha-1). Seed cotton yield varied between 16.3 and 22.0 q ha-1(mean=17.8q ha-1). Results revealed that average yield gap assessed against yield potential for pigeon pea was 53.3%,compared with only 25.2% for Bt-Cotton. Yield gap estimated against national average was however oflower magnitude for pigeon pea (3.8%). Estimation of yield gap against state average further recapitulatesthe similar trend indicating yield gap of 18.5%. Conversely, the pigeon pea grain yield was higher by 3.4 qha-1 when compared with the district average. On the other hand, mean Bt-Cotton seed yield recorded washigher than the national, state and district average. Average net returns for pigeon pea were ` 17.6 X 103 ha-1, compared with Rs. 34.4 X 103 ha-1 for the Bt-Cotton. Economic efficiency was higher for Bt-Cotton (`201 ha-1 d-1), compared with the pigeon pea (` 124 ha-1 d-1). One half of the sample farmers reported thatpigeon pea cultivation has medium level of problem solving ability. More than one half of the respondent(56%) farmers perceived sustainability of pigeon pea cultivation as of medium level. Farmers perceived(56%) pigeon pea as non-practical alternative to Bt-cotton due to lower economic yield. Only 16 per cent ofthe respondent farmers showed high level of preference toward pigeon pea over Bt-cotton.